Wykorzystanie elektronicznej wymiany danych w wybranych przedsiębiorstwach - Fajczak-Kowalska, Anita (Gospodarka w Praktyce i Teorii, 2012)
IT systems that use electronic data interchange standards significantly contribute to the development of companies. This is due to the possibility for increasing the efficiency of data processing, which in today’s economic relations is the key to the smooth functioning of the market. The examples of companies that use EDI systems testify to the fact that the progressive computerization is a prerequisite for harmonious action, and more and more advanced solutions are highly convenient in terms of corporate governance generally understood.